2019
DOI: 10.21608/aasj.2019.60556
|View full text |Cite
|
Sign up to set email alerts
|

Direct and correlated responses from selection for early sexual maturity in Japanese quail

Abstract: Base population after third generation of selection conclude total number of 788 birds at 6 weeks of age were used in this study and randomly assigned to two mating groups. First groupe was selected for early age at sexual maturity (EASM) and the second was as a control line (RBC) to study the direct and correlated responses for this direct of selection. The results can be summarized as follow: 1. EASM was highly significantly (P≤0.01) decreased from 39.54 days to 35.23 days. 2. The actual and the expected sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Ramzy et al 48 reported that cumulative selection response to selection for early sexual maturity decreased EW from 10.74 to 10.04 g but BWSM increased from 136.32 to 139.32 g after four selected generations in Japanese quail.…”
Section: Resultsmentioning
confidence: 99%
“…Ramzy et al 48 reported that cumulative selection response to selection for early sexual maturity decreased EW from 10.74 to 10.04 g but BWSM increased from 136.32 to 139.32 g after four selected generations in Japanese quail.…”
Section: Resultsmentioning
confidence: 99%
“…The usefulness of selection procedures for improving productive or reproductive traits depends not only on the direct response itself, but also on the relevant changes in other economic traits due to the response associated with selection. However, selection for body weight may indirectly affect other traits that were not considered in the selection program because the improved trait is correlated with these traits (Abd El-Ghany, 2005;Kosba et al, 2002, andGhanem et al, 2007;Saleh et al, 2008;Abd Elkarim and Ashour, 2014;Ramadan et al, 2014;Ashour et al, 2015;and Ramzy et al, 2019).…”
Section: Introductionmentioning
confidence: 99%